Pemanfaatan Aplikasi Elektronik Kartu Menuju Sehat (E-KMS SIKELA) Sistem Kesehatan Lansia di wilayah kerja Posyandu Rumbai Bukit - Asep Marzuki; Bobi Handoko; Alfitri Yana Yunita (Komunitas Dosen Indonesia, 2025)
Rumbai Buki Health Center Health Cadres are spread across each posyandu work area. The cadres accommodate toddler and elderly posyandu. One very basic problem in the elderly is health, so efforts are needed to improve the health conditions of the elderly group. The existing posyandu cadres have an average education below high school. There are partner problems, namely the lack of ability to provide health services, such as poor communication skills, lack of knowledge about elderly health, lack of knowledge in screening the elderly Health Card, and lack of innovative activities from cadres. In addition, supporting equipment such as height meters, body weights, thermometers, sphygmomanometers, stethoscopes, and measuring devices for blood sugar, cholesterol, and uric acid levels are still very minimal. Problems in the field of information technology also exist, where recording of elderly health administration data is still done manually. The purpose of this PKM activity is to overcome problems in elderly posyandu cadre partners in Rumbai Bukit village, namely efforts to improve the health of the elderly through training and counselling to elderly cadres, counselling to the elderly, procurement of health support equipment, and designing information systems for computerized administrative management. The results of the service carried out showed that the elderly data totalled 52 people, consisting of 4 men and 48 women.